Spatial Price Discrimination with Heterogeneous Products - Anderson, Simon P.; de Palma, Andre (Review of Economic Studies, 1988)
Product heterogeneity is introduced into the context of spatial price discrimination. Many of the strong properties of the standard homogeneous goods case (which are attained as a limit case here) are shown to be no longer valid. In particular, the social optimum is no longer sustainable as a market equilibrium unless products are either identical or else very different.